Fixed Exchange-Rate Policy and Real Wage Growth: Quasi-Experimental Evidence - Corrado Andini (Institute for the Study of Labor (IZA), 2014)
Using Difference-in-Differences estimation and data from the European Community Household Panel, this paper suggests that the fixed exchange-rate policy adopted by Italy in the 1997-2000 period has reduced the real hourly wage growth of Italian full-time workers with permanent contracts, on average, by 3%. Yet, the cost of the policy has been ultimately paid by the private sector where real wage growth has decreased by 5.4%.
Keywords: J31; C23; 330; difference-in-differences; productivity; wages